The Role of Technology in Improving Employee Performance of Gypsum Installation MSMEs - Irfani, Nizam; Soeprijatno, Edy Djoko (Universitas Nusantara PGRI Kediri, 2025)
Research aim : This study aims to analyze the role of technology in improving employee performance and productivity in Micro, Small and Medium Enterprises (MSMEs), especially in the gypsum installation sector.Design/Methods/Approach: The research results found that the use of modern tools, such as battery-powered drills and standard scaffolding, can increase work efficiency and speed up the gypsum installation process. However, lack of training is a major barrier to technology implementation.Research Findings: This research uses a qualitative approach through case studies and interviews with MSMEs engaged in gypsum installation. Data was collected through structured interviews and direct observation to assess the impact of technology adoption on efficiency and work processes.Theoretical contribution/Originality: This study contributes to the literature on MSMEs by highlighting the unique challenges faced by traditional industries in adopting modern technologies. The study also offers a framework for understanding how focused training can facilitate technology transition.Practitioner/Policy Implications: This study recommends policy interventions, such as subsidies for technology tools and industry-specific training programs, to accelerate technology adoption. Practical implications include the importance of managerial support and ongoing skills development to ensure successful implementation.Research limitations: This research was conducted on a small sample, namely MSMEs in the gypsum installation sector, so the results cannot be generalized. Further research is expected to include a larger sample.